Building Bridges: Challenges to navigating the interstices of Psychology, Neuroscience, and Conflict Resolution. - Feldman, Mallory J. (Tufts Archival Research Center, 2016)
This thesis discusses one of the first data sets designed to help identify and outline challenges to integrating Psychology, Neuroscience, and Conflict Resolution. By engaging these challenges, scientists and practitioners may become better equipped to navigate the interstices of sectors and ultimately to communicate and collaborate better- thereby improving understanding of, and work toward, a more strategic Conflict Resolution. The challenges presented in this paper include those of culture, differing methodologies, scaling, frame of reference, status, accessibility, and language.